Lack of Defects in Androgen Production in Children with Hypospadias - Holmes, Nicholas M.; Miller, Walter L.; Baskin, Laurence S. (The journal of clinical endocrinology and metabolism, 2004)
Formation of the male urethra requires the synthesis of testosterone, its activation to dihydrotestosterone (DHT) in genital skin, and binding of DHT to the androgen receptor. Defects in any of those steps can cause hypospadias. To determine whether defects exist in the production of androgens in individuals with hypospadias, we examined enzymatic function of 3β-hydroxysteroid dehydrogenase (3βHSD), P450c17 (17α-hydroxylase and 17,20 lyase activity), and type 3 17βHSD. Sixty-eight subjects participated in the study: 48 patients had hypospadias, and 20 had normal male genitalia. Subjects were stratified into groups based on age and severity of hypospadias, as defined by location of the urethral meatus after correction of penile curvature. Hormonal values in boys with hypospadias were compared by nonparametric analysis with those in age-matched controls. Controls excluded individuals with cryptorchidism, micropenis, known endocrine defects, or receiving steroid supplementation. Morning fasting serum levels of pregnenolone, progesterone, 11-deoxycorticosterone, 17-hydroxypregnenolone, 17-hydroxyprogesterone, 11-deoxycortisol, cortisol, dehydroepiandrosterone, androstenedione, androstenediol, testosterone, and DHT were determined. To focus on the proximal steps in androgen biosynthesis, 12 individuals with hypospadias underwent standard ACTH stimulation. No significant differences in the androgen precursors and metabolites were found between controls and individuals with hypospadias. The response to ACTH was variable without a significant difference between the patients with different degrees of hypospadias and/or published controls. These data indicate that enzymatic defects in the steroidogenic steps from cholesterol to DHT are not a common etiology of hypospadias. Routine abnormalities in the androgen biosynthetic pathway are an unlikely cause of any degree of hypospadias in boys without accompanying cryptorchidism or genital malformations.